The learning of endangered mother tongue languages of minority, immigrant communities in multilingual contexts: The case of Malayalam in Malaysia - Nambiar, M.K. (2008)
Research (Nambiar, 2007) shows that Malayalees, a minority, an immigrant community in multilingual and multiracial Malaysia, are shifting away from their mother tongue, Malayalam, towards English and Malay. One of the main reasons, is lack of the proficiency in the mother tongue, particularly among the younger generations. This paper examines the reasons why learning of the ancestral language has not been successful and what remediation measures that can be taken. While a number of factors such as lack of government support, paucity of trained teachers, out-dated teaching methodology, time and transport constraints can account for the lack of language learning success, the underlying factor seems to be the low priority accorded to language preservation by the community itself. Hence, there is an urgent need to raise the awareness of the community regarding the significance of their ancestral language in preserving their unique identities as Malaysian Malayalees before instituting a number of language learning initiatives. These include a centralized language curriculum, up-to-date language teaching methodology, well-trained teachers, use of innovative teaching materials, as well as the setting up of learning institutions like a kindergarten and school where Malayalam teaching/learning can be given its due.